Digital Competence Profiles in Education - D. A. Vilyavin; N. V. Komleva; N. A. Mamedova; A. I. Urintsov (Открытое образование (Москва))
Purpose of research. The trend of personalization of learning forms a demand for the development and implementation of software tools for processing the digital footprint of the learner, to manage his/her educational trajectory. In combination with decentralized identification technologies, such software tools assume a more active role of the learner in the creation of his/her personal learning trajectory. Additional challenges for the developed software tools are the functional requirement to ensure the independence of learner profile data from individual educational services, while at the same time complying with the standards of information security of working with data. The purpose of this research is to expand the understanding of the possibility of modifying online learning by including distributed solutions in the field of information technology application in education.Materials and methods. The paper describes in detail the solutions developed by the authors for software implementation of a digital profile of learner's competencies - a decentralized application designed to store data of learning activity and confirmed qualifications aggregated from various external educational platforms and services. When forming these solutions, the authors proceeded from the advantages of using a decentralized approach to software development. The methodological basis of the research is represented by a set of approaches and technologies that support the logic of the software development process - distributed registry technology, digital identification approach, credentials storage standard.Results. The authors substantiate the choice of solution for software implementation of digital competence profile: SSI approach will provide decentralized identification of digital footprint data beyond the boundaries of individual educational platforms and services; application of the standard of verifiable VC credentials will create conditions for decentralized storage of learning activity data. The results of the study may be of practical interest for the administration of domestic educational organizations, administration of educational platforms and educational services implementing online learning programs for effective and secure management of each individual student's digital footprint data, creating an individual educational trajectory in his/her interests and confirming competencies.Conclusion. Implementation and scaling of the digital competence profile are aimed at ensuring the identification, safe storage, and effective management of the learner's digital footprint data, which can be used to create an individual learning trajectory. The digital competence profile will allow to realize the function of confirming any forms of activity, the nature of interaction of the learner with the functions of the educational service, as well as allow the learner to control and manage the use of the information placed in the digital profile. As part of the whole, the digital profile is considered in the overall architecture of the information system, which implies the interaction of the software application with other subsystems, including in the structure of the educational platform. The scheme of interaction demonstrated for the digital educational platform “Digital Tutor” developed at the Plekhanov Russian University of Economics. Additional research requires tools for controlling the activity and motivation of the learner to formalize his/her active role in the issues of personal learning trajectory management.